Studi potensi pengembangan wisata di Banjar Gunung Kangin, Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan, Bali - I Gede Made Indra Adi Brata; I Made Sukewijaya; I Made Agus Dharmadiatmika (Jurnal Arsitektur Lansekap, 2025)
Banjar Gunung Kangin has an area of 1.7 km2 located at an altitude of 700–850 masl and is planned to be developed into a tourist destination based on its natural resources. This study aims to determine natural resources that have the potential to be developed into tourist attractions that support tourism development in Banjar Gunung Kangin, development potentials, and solutions so that the direction of development is appropriate and does not damage the surrounding environment so that it becomes a sustainable tourist destination. The research method used is a survey-descriptive method. The data collected is in the form of primary and secondary data. The techniques used to collect data in this study are observation, questionnaires, interviews, and literature studies. Based on the results of the study, it is known that geographical location, climate and weather, topography, landforms, vegetation, and animals are natural resources that have the potential to be developed into tourist destinations. The results of the inventory and analysis of the potential and constraints at the research location can be drawn into a synthesis that is made to maximize the potential of natural resources owned and minimize constraints at the research location by dividing space in the area of development of tourist destinations into two, namely public space and semi-conservation space. Recommendations for tourist attractions that can be developed at Banjar Gunung Kangin are jogging tracks, camping grounds, rural tourism, hidden waterfalls, hidden canyons, and religious tourism at Banjar Gunung Kangin. The hope in developing this tourist destination area is not to damage the existing ecosystem, not to damage the environment, and to be able to maintain the existing natural resources.